Guillain-Barré Syndrome Associated with Acute HEV Hepatitis (Ibrahim Medical College Journal, 2009)
Guillain-Barré Syndrome (GBS) otherwise known as Acute Inflammatory Polyneuritis, characterized by acute progressive limb weakness and aretlexia, is the prototype of a post infectious autoimmune disease. Two-thirds of the cases of GBS emerge from viral or bacterial infection. In August 2006, a 20 year old man presented at ICU, BIRDEM Hospital with a history of brief icteric illness followed by progressive bilateral symmetrical hypotonic aretlexic muscular weakness, bilateral infra-nuclear facial palsy and bulbar weakness. Later on, he was diagnosed as a case of GBS and acute hepatitis E. Up till now, only three cases of GBS associated with hepatitis E have been reported in the medical literature world wide. This is probably the 4th case to be reported. Ibrahim Med. Coll. J. 2008; 2(1): 32-34 Key words: Guillain-Barré Syndrome, acute hepatitis E doi: 10.3329/imcj.v2i1.2930